(untitled) (Global Journal of Human-Social Science, 2019)
This research described the basic inspiration behind the implementation of a humanistic approach to the principal’s leadership and the steps of the principal’s humanistic approach that have an impact on optimizing the implementation of the program for strengthening character education. This research used a qualitative approach, a case study design. To achieve the research objectives, data collection was performed through in-depth interviews, participant observation, and documentation studies. Data analysis used a modified analytic analysis method. Data validity was based on the level of credibility, transferability, dependability, and confirmability. The research findings explained that the principal’s humanistic approach is inspired by personal excellence (integrity, wholeness, and self-authenticity) and the humanistic spirituality of inspirational figures.